Assessment of sustainability in cocoa farms in Ecuador: application of a multidimensional indicator-based framework - Marco Heredia-R; Irene Blanco-Gutiérrez; Paloma Esteve; Laura Puhl; Cristian Morales-Opazo (International Journal of Agricultural Sustainability)
Cocoa is one of Ecuador’s main export products. Over the last decades, cocoa production in the country has increased considerably, making it the largest producer of cocoa in Latin America. However, this increase has been accompanied by environmental degradation, endangering the sustainability of cocoa cultivation. This study utilizes an innovative indicator-based framework to evaluate the sustainability performance of fine flavour and CCN-51 cocoa farms in Ecuador, across economic, social, environmental, nutrition and health, and governance dimensions. Data were collected from 169 farms in Manabí Province and multiple statistical tests were employed to discern sustainability scores. The results highlighted significant differences in sustainability between the two cocoa production systems, influenced by factors such as ethnicity, age, and level of education. A 53% variation in sustainability scores between the fine flavour and CCN-51 cocoa farms was identified. The association of lower sustainability scores with limitations of physical and financial capital provides insights for enhancing sustainable cocoa farming in Ecuador.